Designing and implementing unemployment benefit systems in middle and low income countries: beyond risk-pooling vs savings - David A. Robalino; Michael Weber (IZA Journal of Labor Policy, 2013)
Several middle income countries are considering reforms to their severance pay regulations to both increase flexibility for firms and better protect workers. Policy discussions then often revolve around whether to adopt an unemployment insurance (UI) scheme or unemployment individual savings accounts (UISAs). Proponents of the first emphasize its ability to pool risks and introduce an element of solidarity. Critics point to its potentially negative effects on labor supply as individuals could have fewer incentives to seek, take or keep jobs. In this paper, we show that UI and UISAs are, in fact, particular cases of a more general design and that the crucial policy choice is in terms of how redistribution - to cover benefits for those who could not save enough - is financed. We outline key features of this general design and identify trade-offs and possible solutions. We then discuss issues related to implementation and show how recent technological developments around biometric identification can facilitate the monitoring of conditionalities related to participation in job-search and training activities.
Keywords: O15; J64; H55; 330; Unemployment benefits; Unemployment insurance; Savings accounts; Risk-pooling; Labor market transitions